2008
DOI: 10.1121/1.3001706
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the optimal signal conditions for recording cubic and quadratic distortion product otoacoustic emissions

Abstract: Odd-and even-order distortion products ͑DPs͒, evoked by two primary tones ͑f 1 , f 2 , f 1 Ͻ f 2 ͒, represent different aspects of cochlear nonlinearity. The cubic and quadratic difference tones ͑CDT 2f 1 − f 2 and QDT f 2 − f 1 ͒ are prominent representatives of the odd and even DPs. Distortion product otoacoustic emissions ͑DPOAEs͒ were measured within a primary level ͑L 1 , L 2 ͒ space over a wide range of f 2 / f 1 ratios to compare the optimal signal conditions for these DPs. For CDT, the primary level di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 54 publications
(32 reference statements)
1
18
1
Order By: Relevance
“…The fairly high standard deviation reflected the interindividual variability. We therefore could not confirm the findings of Bian and Chen (2008). They reported a shallow notch for QDPOAE amplitudes around an f 2 /f 1 ratio of 1.25 (albeit at 4 kHz and measured in only 8 subjects).…”
Section: General Considerationscontrasting
confidence: 73%
See 1 more Smart Citation
“…The fairly high standard deviation reflected the interindividual variability. We therefore could not confirm the findings of Bian and Chen (2008). They reported a shallow notch for QDPOAE amplitudes around an f 2 /f 1 ratio of 1.25 (albeit at 4 kHz and measured in only 8 subjects).…”
Section: General Considerationscontrasting
confidence: 73%
“…This discrepancy is not surprising as best f 2 /f 1 ratios for QDPOAEs in humans can differ with primary tone frequencies (own unpublished observation). During biasing, primary tone levels were set to l 1 ¼ l 2 , which gives, according to Bian and Chen (2008), optimum QDPOAE levels. l 1 and l 2 were set to 70 dB SPL, which resulted in acceptable SNRs in all subjects.…”
Section: General Considerationsmentioning
confidence: 99%
“…Maximizing DPOAE amplitudes increases the sensitivity of DPOAE measurements for detecting cochlear damage (Whitehead et al, 1995a,b;Kummer et al, 1998). It has been reported that for optimal stimulation the difference between the stimulus levels decreases with increasing L 2 (Gaskill and Brown, 1990;Dhar et al, 1998;Bian and Chen, 2008) and approaches zero (i.e., L 1 approaches L 2 ) at high stimulus levels (Whitehead et al, 1995a,b;Neely et al, 2005). Specifically, for a given L 2 , Whitehead et al (1995b) have reported that the optimal value of L 1 , denoted by L 1;opt , is approximately linearly proportional to L 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in condition 1, the AM tone served as the f 1 ; while it acted as the f 2 in condition 2. These frequencies were determined such that the f 2 /f 1 ratios in both conditions were around 1.22 to evoke a relatively large CDT (Bian and Chen, 2008) and to reduce the influence of the CDT generated from a reflection source located at its CF place in the cochlea (Knight and Kemp, 2001;Dhar et al, 2005). The AM tone was created by multiplying two sinusoids, a carrier and a modulator with frequencies of f c and f m , according to the following formula:…”
Section: Signal Conditionsmentioning
confidence: 99%
“…However, behaviors of DPOAEs evoked by AM tones have never been systematically investigated. Since the f 1 and f 2 have different roles in the generation of DPOAEs (Bian and Chen, 2008), they may have different effects on DPOAEs when they are amplitude modulated. In this study, the two primaries were replaced with AM tones individually and the signal parameters were systematically varied.…”
Section: Introductionmentioning
confidence: 99%